Dependence of the relationship between the tropical cyclone track and western Pacific subtropical high intensity on initial storm size: A numerical investigation. Issue 22 (21st November 2015) - Sun, Yuan; Zhong, Zhong; Yi, Lan; Li, Tim; Chen, Ming; Wan, Hongchao; Wang, Yuxing; Zhong, Kai
Abstract: A suite of numerical experiments were conducted to investigate the sensitivity of the tropical cyclone (TC) motion—western Pacific subtropical high (WPSH) intensity relationship to initial storm size. Two TC cases, Songda (2004) and Megi (2010), were studied. It was found that with the increase of initial storm size, the main body of the WPSH tends to withdraw eastward and the TC tends to turn northward earlier. The involved physical mechanism was investigated. Rather than the change of the beta effect due to storm size change, it is the change of the geopotential height in the TC outer region that is critical for the different TC tracks between the sensitivity experiments. Due to increase of the initial storm size, the inflow mass flux entering the TC region increases, leading to a significant decrease in 500 hPa geopotential height in the TC outer region after 2–3 day integration. As a result, the simulated intensity of the WPSH over its fringe close to the TC decreases notably when the WPSH edge is within the TC outer region. Such a decrease leads to a break of WPSH. Subsequently, the TC turns northward toward the break of the subtropical high. This further weakens the intensity of the WPSH over the region close to the TC. The result helps us better understand the relationship between the TC track and WPSH intensity. It also indicates that a proper representation of initial storm size is important for realistic prediction of TC track and the change of the WPSH. Key Points: Simulated TC track and WPSH are sensitive to initial storm size Large TC tends to decrease WPSH intensity and thus force TC turn northward Differences are attributed to the inflow mass flux entering into TC region